2001
DOI: 10.1086/318821
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and Genotypic Characteristics ofEscherichia coliStrains of Non–EnteropathogenicE. coli(EPEC) Serogroups that Carryeaeand Lack the EPEC Adherence Factor and Shiga Toxin DNA Probe Sequences

Abstract: This study was conducted to characterize the virulence potential of 59 Escherichia coli strains carrying EAE and lacking the enteropathogenic E. coli adherence factor and Shiga toxin probe sequences. In hybridization studies, all strains carried the locus of enterocyte effacement (LEE)-associated DNA sequences. Of the other 15 virulence DNA sequences tested, HLY was the most frequent (44.1%); 17 combinations of these sequences were found, but strains carrying EAE only (EAE profile) were the most frequent (35.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
146
2
48

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(208 citation statements)
references
References 44 publications
12
146
2
48
Order By: Relevance
“…Earlier studies on the adherence pattern of eae þ EAF À isolates gave variable results and depended on the method used, because many isolates did not adhere when the 3-h method was used [39,43,44]. However, most atypical EPEC isolates adhered in a localised way when incubated for 6 h with a washing step at 3 h [37,38,40,41,[45][46][47][48]. Such adherence was termed localised-like to distinguish the adherence pattern from that of typical EPEC strains, which can be detected after incubation for 3 h, and is characterised by the presence of more compact microcolonies of bacteria on most cells [48].…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies on the adherence pattern of eae þ EAF À isolates gave variable results and depended on the method used, because many isolates did not adhere when the 3-h method was used [39,43,44]. However, most atypical EPEC isolates adhered in a localised way when incubated for 6 h with a washing step at 3 h [37,38,40,41,[45][46][47][48]. Such adherence was termed localised-like to distinguish the adherence pattern from that of typical EPEC strains, which can be detected after incubation for 3 h, and is characterised by the presence of more compact microcolonies of bacteria on most cells [48].…”
Section: Discussionmentioning
confidence: 99%
“…Several case-control studies including eaeA-positive EPEC indicated that EAF plasmid-positive isolates were significantly associated with diarrhoea [32,33]. However, atypical EPEC have also been reported as being the sole causative agent of acute diarrhoeal disease in several countries [32,[34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…Estudos têm demonstrado que amostras de EPEC atípicas são capazes de apresentar, além do padrão LAL, os padrões de adesão agregativa, difusa, localizada, além de algumas amostras se mostrarem incapazes de aderir em células epiteliais in vitro (VIEIRA et al, 2001;DULGUER et al, 2003;GOMES et al, 2004;HERNANDES et al, 2006). …”
Section: Interação De Epec Com a Célula Epitelialunclassified
“…Não é conhecida a razão deste "atraso" na adesão bacteriana e consequentemente na formação da lesão A/E causada por EPEC atípica. Vários estudos têm demonstrado que amostras de EPEC atípica são capazes de apresentar além do padrão LAL os padrões de adesão agregativo, difuso e localizado (PELAYO et al, 1999;SCALETSKY et al, 1999;VIEIRA et al, 2001;DULGUER et al, 2003;GOMES et al, 2004;HERNANDES et al, 2008 (PELAYO et al, 1999;VIEIRA et al, 2001;DULGUER et al, 2003;SCALETSKY et al, 2005;BAI et al, 2007;HERNANDES et al, 2008;MOREIRA et al, 2008 ALBERT et al, 1995;ALBERT, 1996;TORRES et al, 2001). No Brasil, são responsáveis por mais de 30% dos casos de diarréia, sendo que os sorotipos O111ab:HNM, O111ab:H2 e O119:H6 são os mais prevalentes na cidade de São Paulo (TRABULSI et al, 1961;TOLEDO et al, 1983;GOMES et al, 1991).…”
Section: Introductionunclassified
See 1 more Smart Citation